ASSESSMENT OF RADIATION RISKS FOR CONSUMTION OF BACKERY CONTAINING STRONTIUM AND CESIUM - Петрусенко, В. П.; Дмитруха, Т. І. (Science-based technologies, 2019)
The article provides analysis of study actuality and importance of environmental risks assessment including radiation risks. Radiation safety is one of the most important tasks related to the life safety nowadays. With development of nuclear power engineering industry in many countries, the real hazard of nuclear pollution of environment and populated areas appears. Therefore the quantitative assessment of nuclear hazards allows it allows not only evaluate hazards level for human health but also determine need for the relevant countermeasures to diminish the environmental risks. In this research work detection of environmental risks arising from consumption of bakery containing radionuclides cesium-137 and strontium-90 is discussed. Those radionuclides have the extended half-life, and their presence in food products, soil and water is a real problem in Ukraine. The article provides the characteristics of radionuclides cesium-137 and strontium-90 and describes the main routs of getting them to environment and into human body. To determine the relevant radiation risk internal exposure factors for certain radionuclides were used. The key criterion at assessment of ecology nuclear hazards is the dose for population; it helps to predict the risks of consequences of radiation. For this purpose the collective and individual doses of internal expose were calculated. Based on these values the collective risks were determined at selected radionuclide levels of cesium137 and strontium-90. These risks affect the collective span of life of certain part of the population as well as they are responsible for the mean loss of life span. The choice of the optimal countermeasures strategy on the polluted territories should rely on the analysis of negative consequences and risks, therefore the quantitative assessment is one of steps to assure the ecological safety.